Neurological syndrome in goats associated with Ipomoea trifida and Ipomoea carnea containing calystegines. (January 2019) - Salinas, Luis Manuel; Balseiro, Ana; Jirón, William; Peralta, Alan; Muñoz, David; Fajardo, Jorge; Gayo, Elena; Martínez, Ileana Zorhaya; Riet-Correa, Franklin; Gardner, Dale R.; García Marín, Juan Francisco
Abstract: A disease characterized by ataxia, tremors and nystagmus had been observed in goats in Nicaragua. The main histologic lesions were loss and neuronal vacuolation of Purkinje cells and Wallerian-like degeneration mainly in the cerebellum, suggesting a glycoprotein storage disease. Ipomoea carnea and Ipomoea trifida found in the paddocks were negative for swainsonine, but contained calystegines at 0.02% and 0.06% suggesting that the disease was caused by these substances, which are competitive inhibitors of β-glucosidase and α-galactosidase activities. Graphical abstract: Image 1 Highlights: Description of poisoning due to Ipomoea spp. only containing calystegines in goats. Ipomoea trifida and Ipomoea carnea, are involved, the first one not previously described. The calystegine content in those plants may be the toxic compound and cause a glycoprotein storage disease.